Development of dental implant coating with minocycline-loaded niosome for antibacterial application - Nattarat Wongsuwan (2020)
© 2020 Elsevier B.V. Peri-implant diseases are mostly caused by a bacterial infection which leads to inflammation and bone loss at and around the implant. In this study, minocycline-loaded niosomes prepared by thin-film hydration method were coated on the dental implant for antibacterial application. Minocycline-loaded-niosomes were characterized for drug loading content, encapsulation efficiency and yield. Result demonstrated that the optimum formulation was 3:1 comprising of span 60 and cholesterol which provided the most drug loading content and encapsulation efficiency. The optimum coating cycles were 120 which could coat the highest content of drug on coated dental implants. In vitro drug release from the coated implants was studied. Antibacterial activity and cytotoxicity of the coated implant were also investigated. Results suggested that minocycline-release from the coated dental implant could be controlled for up to 7 days which was a crucial period after implantation. During this time, inhibition of Porphylomonas gingivalis was also noticed. In vitro cytotoxicity study revealed that the coated implant was non-toxic to osteoblast cells. Hence, results suggest that this coating strategy can be used for antibacterial coating of medical devices.